SYMBOLISM OF BODY IN FRENCH PROVERBS AND ITS EQUIVALENTS IN SUNDANESE: A CULTURAL SEMANTICS STUDY - Nurul Saefullah; Risa Rosalina (Metahumaniora, 2023)
A proverb is a type of folklore that is passed down from one generation to another as a tradition. In its formation, proverbs use expressions and word choices related to life around the community and cannot be separated from the cultural values it wishes to express. One of the constituent elements is the use of the parts of the human body which philosophically contain a symbolic meaning that can be interpreted. In this paper, French proverbs containing these terms are described, their meanings examined, and then compared with Sundanese proverbs. The aim is to find the universal values of proverbs from different cultural backgrounds. This research was conducted using a descriptive-comparative method with a cultural semantics approach. The results of the study show that the parts of the human body used in French proverbs are the names of the parts of the human body themselves, both the external parts and the organs inside the human body. Apart from that, the functions of the parts, their abilities, or disabilities are also found in the data. From a comparative perspective with Sundanese proverbs, French proverbs have equivalent meanings and values expressed in various ways.